Law no. 154 of the year 2022 On Amending Certain Provisions of the Money Laundering Combat Law Promulgated by Law No. 80 of the year 2002 = قانون رقم 154 لسنة 2022 بتعديل بعض أحكام قانون غسل الأموال الصادرة بالقانون رقم 80 لسنة 2002 (2025)
English & Arabic